The Implementation of Securing Plaintext File Using Cryptography Method in Web Based Environment - Hasnira, Md. Lazim (2004)

(untitled)
The objective of this research in primarily to find the best fit crytography system that can encrypt and decrypt the extension file .doc, implement it in a simple application which works similar to email and construct and run a set of evaluation to securing plaintext file in a web based environment. The methodology and testing procedure which are used during this evaluation is based on a simulation model. Result from the evaluation set constructed is found able to show the performance of the cryptography system. ClipSecure is rate to be the best fitted features of cryptography system in this project scope for it has choices of nine algorithms, plus a hardcore mode and support for both message and file encryption.